HARMFUL ASPECTS OF EPILEPSY - Djurabekova Aziza Taxirovna; Amonova Zakhro Kakhramonovna; Akmaljon Akhmatjonovich Gaybiyev; Amonova Zilola Kahramonovna (PEDAGOGS, 2024)
Abstract: Epilepsy is a neurological disorder characterized by recurrent seizures caused by abnormal electrical activity in the brain. Although epilepsy affects people in different ways, there are several toxicities associated with the condition that can affect people's quality of life. In three articles, we will look at some of the harmful factors of epilepsy and the problems that people living with this disease face.